2019
DOI: 10.1038/s41598-019-44661-x
|View full text |Cite
|
Sign up to set email alerts
|

The ion channels and transporters gene expression profile indicates a shift in excitability and metabolisms during malignant progression of Follicular Lymphoma

Abstract: The definition of the gene expression profile of genes encoding Ion Channels and Transporters (ICT-GEP) represents a novel and attracting aspect in cancer. We determined the ICT-GEP of Follicular Lymphoma (FL), and compared it with that of the more aggressive Diffuse Large B Cell Lymphoma (DLBCL). cDNA microarray data were collected both from patients enrolled for this study, and from public datasets. In FL the ICT-GEP indicated the overexpression of both the K + channel encoding gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
(53 reference statements)
4
13
0
Order By: Relevance
“…The mitochondrial remodelling in KRAS mutated-BRAF wild-type CRC agree with Warburg's hypothesis, suggesting that the scenario might be different to that observed in other tumours, as in the case of the relevant role of OXPHOS in lymphomas [46].…”
Section: Discussionsupporting
confidence: 77%
“…The mitochondrial remodelling in KRAS mutated-BRAF wild-type CRC agree with Warburg's hypothesis, suggesting that the scenario might be different to that observed in other tumours, as in the case of the relevant role of OXPHOS in lymphomas [46].…”
Section: Discussionsupporting
confidence: 77%
“…4g). Some of the genes associated with these 16 sites included PLEKHA7, AP1M2, ATP9A, and ARVCF known to be downregulated in breast and prostate cancer (data not shown), as well as other cancers [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this process is widely involved with DLBCL metabolic reprogramming 29 . Related ion binding pathways, specifically genes related to ion channels and transporters, as have been associated with DLBCL development and relapse in patients 30 . Other pathways such as neurotrophins and Trk signaling 31 and Fc epsilon receptor signaling 32 have been shown to be involved in DLBCL resistance to therapeutic drugs.…”
Section: Resultsmentioning
confidence: 99%